SOCIAL CONSTRUCTION OF MASS MEDIA ON VOTER PREFERENCES IN THE 2024 GENERAL ELECTION - Mukti, Imam (CORE: Journal of Communication Research, 2024)
This research aims to explore in depth how mass media shapes voter preferences in the 2024 General Election in Indonesia. The method used in this research is qualitative with a case study approach. This study analyzes the social construction carried out by the mass media on political issues, candidates and political parties. Data was collected through in-depth interviews with voters and analysis of mass media content. The research results show that mass media has the power to shape voter preferences through framing , agenda setting , and priming . Mass media not only functions as a transmitter of information, but also as an agent of social construction that can influence voters' perceptions and decisions in determining their political choices.